Nano-Pico Satellite Actuator Fault Diagnosis Based on Adaptive Observer. (August 2019) - Fei, Y; Meng, T; Jin, Z H
Abstract: This paper concerns with actuators fault diagnosis of nano-pico satellite, and a double adaptive estimation algorithm is proposed. Based on the non-linear mathematical model of reaction flywheel, a parameterized description method of flywheel fault type is established. Using the input and output information of the flywheel, a local adaptive observer is constructed and can identify the fault type of the flywheel. A global adaptive observer based on the satellite dynamics model uses the gyroscope sampling signal and the estimation of local observer as inputs, so failure moment of the other actuator can be identified. Combining two observers' identification results, the fault diagnosis of flywheel and the other actuator can be completed. In this paper, a control system composed of reaction flywheel and magnetorquer is simulated. Results show the effectiveness of proposed method for nano-pico satellite actuator fault diagnosis.